Electrophysiological findings show generalised post-photoreceptoral deficiency in macular telangiectasia type 2. Issue 1 (7th June 2017) - Ledolter, Anna A; Holder, Graham E; Ristl, Robin; Schmidt-Erfurth, Ursula; Ritter, Markus
Abstract : Background: Photoreceptor damage, reported in single observations, has been suggested to contribute to the disease pathogenesis in macular telangiectasia type 2 (MacTel2). The purpose of this study was to ascertain whether the photoreceptor or post-photoreceptoral function is affected in MacTel2 and could be detected using electrophysiological examination. Methods: Thirty-five eyes from 18 patients (15 men, aged 60.1±9.6 years, range 38–77 years) with MacTel2 were included in the study. All patients underwent standard ophthalmic examination followed by pattern electroretinography (PERG) and full-field ERG. The data were compared against 22 normal control subjects (10 men, age 59.83±6.28 years, range 48–76). Results: Mean PERG P50 amplitude and peak time in patients with MacTel2 did not differ significantly from control values (p>0.2) but P50 amplitude was subnormal in three patients. The mean scotopic rod b-wave amplitude was significantly lower in patients than in healthy controls (p=0.027). A lower dark-adapted 10.0 b-wave (p=0.06) but not a-wave amplitude (p=0.58) was present in patients with MacTel2. Photopic single-flash a-wave and b-wave amplitudes did not differ between patient and control groups (p=0.2 and 0.3), but 30 Hz flicker peak time was significantly later in patients with MacTel2 with no effect on amplitude (p=0.04 and 0.7). Conclusion: Both scotopic (rod system dominated) and photopic ERGs (cone system) are consistent with post-photoreceptoral dysfunction. There was no electrophysiological evidence of dysfunction at the level of the photoreceptor.